(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Out of six hilsa sanctuaries in Bangladesh, the newly established Hizla- Mehendiganj sanctuary is significantly lacking in data in terms of fish diversity and physicochemical properties. Therefore, the present study aims to assess water quality variables and fish biodiversity of the Hizla-Mehendiganj hilsa sanctuary. Water and fish samples were collected from different sites within and outside the sanctuary. Physicochemical variables such as dissolved oxygen (DO), temperature, pH, electrical conductivity (EC), total dissolved solids (TDS) and transparency were measured and fish biodiversity was estimated using different richness and evenness indices. The mean DO, temperature, pH and transparency inside the sanctuary were 5.6 ± 0.1 mg/l, 29.1 ± 0.7°C, 8.3 ± 0.05 and 20.5 ± 2.3 cm, respectively which were nearly similar to the estimated values of those variables of the outside sanctuary. This study found a total of 374 individuals of 21 fish species under 6 orders and 14 families. According to the IUCN report 2015, this study found that 76.19, 9.52 and 4.76% of these species are listed in the Least Concern, Endangered and Vulnerable category, respectively. Within the sanctuary, 76 individuals of 13 fish species under 4 orders were recorded which was lower than the recorded number of total individuals and number of species outside the sanctuary sites. Within the sanctuary, estimated Shannon’s, Simpson’s, Margalef’s and Buzas and Gibson’s indices were 1.881, 0.214, 1.881 and 1.156, respectively which indicated comparatively moderate diversity. The highest biodiversity was found in the Ilisha river near Rukundi, outside the sampling site of the sanctuary. The findings of this study can be used for future biodiversity assessments, conservation and impact assessments of the Hizla- Mehendiganj hilsa sanctuary. Dhaka Univ. J. Biol. Sci. 31(2): 289-301, 2022 (July)